PERAN SEKOLAH LANSIA TANGGUH DALAM PEMBERDAYAAN SOSIAL DAN EKONOMI LANSIA DI KELURAHAN SURODINAWAN, KOTA MOJOKERTO - Aulia Dhuhita, Chandramaya; Hadi, Nur (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2025)
Sekolah Lansia Tangguh is a program organized by the National Population and Family Planning Agency (BKKBN) in collaboration with the Indonesia Age-Friendly  Foundation (IRL). The study aims to analyze the implementation of the Sekolah Lansia Tangguh program related to the empowerment of the elderly in the social and economic fields in Surodinawan Village, Mojokerto City and the impact of Sekolah Lansia Tangguh on the social and economy of its participants. This research method uses qualitative with a case study approach. Researchers collected data through in-depth interviews with administrators and participants in the Tangguh School for the Elderly, besides that researchers also collected data through literature studies and documentation. The results of this study indicate that the Sekolah Lansia Tangguh implemented by Surodinawan Village has successfully contributed to the ability of the elderly to socialize in the community and improve social networks through mutual cooperation activities and playing games. However, economic empowerment in the form of planting kale, chilies and tomatoes has not gone well, the main obstacles are the lack of interest of the elderly in distribution, plants that die easily and limited business capital assistance from the village. This study concludes that Sekolah Lansia Tangguh has an important role in improving the quality of life of the elderly from the social aspect but has not been successful in the economic aspect.